White Matter Microstructure Changes and Cognitive Impairment in the Progression of Chronic Kidney Disease - Liu, Mengchen; Wu, Yunfan; Wu, Xixin; Ma, Xiaofen; Yin, Yi; Fang, Huamei; Huang, Sihua; Su, Huanhuan; Jiang, Guihua (Frontiers in Neuroscience, 2020)
Background Cognitive impairment is a well-defined complication of chronic kidney disease (CKD), but the neural mechanisms are largely unknown. Objectives The study aimed to assess white matter (WM) microstructure changes and their relationship with cognitive impairment development during CKD progression. Methods DTI datasets were acquired from 38 patients with CKD (19 patients were at stage 3; 19 patients were at stage 4) and 22 healthy controls (HCs). Tract-based spatial statistics (TBSS) were implemented to assess the differences in WM integrity among the three groups. The associations between abnormal WM integrity and clinical indicators (digit symbol test scores, the type A number connection test scores, hemoglobin, serum urea, serum creatinine, serum calcium, and serum potassium levels) were also computed. Results Compared with patients with CKD at stage 3 and HCs, patients with CKD at stage 4 showed significantly lower fractional anisotropy (FA) and higher mean diffusivity (MD) in the corpus callosum(CC), anterior thalamic radiation, inferior fronto-occipital fasciculus, inferior longitudinal fasciculus. Correlation analysis showed that the MD in the genu of CC was negatively associated with the digit symbol test scores (r = −0.61, p = 0.01), and the FA in the left anterior thalamic radiation was positively associated with the level of serum calcium(r = 0.58, p = 0.01). Conclusions Patients with non-end-stage CKD have multiple abnormalities in WM regions. DTI metrics change with the progression of CKD and are primarily associated with cognitive impairment. The reduced integrity of WM tracts may be related to a low level of blood calcium.